Glycosylated lysosomal membrane protein promotes tissue repair after spinal cord injury by reducing iron deposition and ferroptosis in microglia - Fangru Ouyang; Meige Zheng; Jianjian Li; Jinxin Huang; Jianan Ye; Jingwen Wang; Yuanzhe Zhao; Fangli Shan; Ziyu Li; Shuishen Yu; Fei Yao; Dasheng Tian; et al. (Scientific Reports)
Abstract Excessive iron deposition can lead to ferroptosis, a form of iron-dependent cell death detrimental to neuronal survival. Microglia have been identified as having a high capacity for iron deposition, yet it remains unclear whether microglia undergo ferroptosis while phagocytosing excessive amounts of iron after spinal cord injury (SCI). Here, we observed scattered iron around the epicenter of the injured spinal cord at 7 days post-injury (dpi) in mice, which then accumulated in the lesion core at 14 dpi. Concurrently, microglia exhibited elevated expression of the iron-storage protein ferritin and were found to undergo ferroptosis between 7 and 28 dpi. Additionally, we noted a gradual decrease in glycosylated lysosomal membrane protein (GLMP) which is associated with iron metabolism in microglia undergoing ferroptosis. In situ injection of AAV9-Cx3cr1-shGlmp-eGFP to knock down GLMP specifically in microglia resulted in a significant increase in iron deposition and ferroptosis, leading to an expanded lesion area, aggravated neuronal loss, and subsequent inhibition of functional restoration. Our findings highlight the crucial role of GLMP in mitigating iron overload and ferroptosis in microglia, thereby contributing to axon retention and locomotor recovery after SCI.